PSYCHOLOGICAL EFFECTS OF STIGMATIZATION ON STUDENTS PURSUING VOCATIONAL EDUCATION IN SECONDARY SCHOOLS, IN NASARAWA LGA, NASARAWA STATE (NAU Journal of Technology and Vocational Education, 2025)
This study examines the psychological effects of stigmatization on students pursuing vocational education in secondary schools within Nasarawa Local Government Area (LGA) of Nasarawa State, Nigeria. The objective was to assess how stigma related to vocational education influences students' self-esteem, emotional well-being, and academic motivation. A sample of 120 students was selected from six secondary schools offering vocational education programs. Data were collected using a structured questionnaire that measured perceived stigmatization, self-esteem, emotional well-being, and academic motivation. The analysis revealed that students who perceived higher levels of stigmatization exhibited significantly lower self-esteem and emotional well-being, as well as reduced academic motivation. Pearson’s correlation analysis showed a strong negative relationship between perceived stigmatization and both self-esteem and emotional well-being. Furthermore, t-tests indicated gender differences in stigmatization, with male students reporting higher levels of stigma and lower self-esteem than their female counterparts. The findings suggest that stigmatization of vocational education is a significant psychological barrier, affecting the mental health and educational outcomes of students. The study concludes by recommending targeted interventions, including educational reforms, enhanced counseling services, and gender-sensitive approaches, to mitigate the negative effects of stigma and promote a more inclusive educational environment.
Keywords: Stigmatization; Vocational Education; Secondary Schools; Psychological Effects; Self-Esteem